BIOCHEMICAL EVALUATION OF ANTIDIABETIC PROPERTIES OF SWERTIAMARIN, A SECOIRIDOID GLYCOSIDE OF ENICOSTEMMA LITTORALE LEAVES, STUDIED IN HIGH-FAT DIET–FED LOW-DOSE STREPTOZOTOCIN-INDUCED TYPE 2 DIABETIC RATS - R, Selvam; K, Muruganantham; S, Subramanian (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Swertiamarin, a secoiridoid glycoside present in the leaves of Enicostemma littorale, is reported to be responsible for its pharmacological and beneficial properties. The present study was aimed to biochemically evaluate the antidiabetic properties of Swertiamarin in high fat diet fed - low dose streptozotocin (STZ)-treated diabetic rats. Methods: High-fat diet-fed low-dose STZ was used to induce experimental type 2 diabetes in rats. Diabetic rats were orally treated with swertiamarin (50 mg/kg b.w./rat/day) for 30 days. The physiological criterions such as food and fluid intake were recorded. Oral glucose tolerance test was performed. The levels of fasting blood glucose, plasma insulin, glycosylated hemoglobin A1c (HbA1c), hemoglobin, and homeostasis model assessment of insulin resistance (HOMA-IR) values were estimated. The activities of key enzymes involved in carbohydrate and glycogen metabolism in the liver and kidney tissues were assayed. The glycogen content in liver tissue was estimated. Result: Oral administration of swertiamarin to diabetic rats established a significant decline in the levels of fasting blood glucose, HbA1c as well as HOMA-IR values and an increase in plasma insulin and hemoglobin levels. The altered activities of key enzymes of carbohydrate and glycogen metabolism in liver and kidney tissues of diabetic rats were restored to near normalcy by swertiamarin treatment. Conclusion: Swertiamarin treatment maintains normoglycemia in diabetic rats by modulating the activities of key carbohydrate and glycogen metabolizing enzymes in the hepatic and renal tissues.